Role of colour in packaging and affect on consumer purchase intention - Jain, Pritesh (2016)
In today's consumption society, buyers are confronted with a substantial choice of product and in this way; the packaging plays important roles as it is a source of information. Packaging is a crucial aspect and consumer buying behaviour is based on packaging and its various elements. The purpose of this study is to understand the role of colour used in packaging aeffcting consumer purchase intention in the soft drink industry, by examining the difference in the response for same colour with different level of hue. The points of focus are how changes in the hue level of colour affect consumer involvement level and their purchase intention for the soft drink.